Particle motion over a plane, which rotates about a horizontal axis and makes a certain angle with it - Pylypaka, S.; Klendii, M.; Trokhaniak, V. (Ye.A.Buketov Karaganda State University Publ., 2019)
Differential equations of relative material particle motion over a plane, which rotates about a horizontal axis, have been set up. Plane location relative to a rotation axis is set by a certain angle, which value can range from zero to ninety degrees. If angle value is equal to zero, a plane passes through a rotation axis; if angle value equals to 90 degrees, it is perpendicular to a rotation axis. The equations have been solved using numerical methods. In case of end positions of an angle, analytical solution has been found.
Көлденең осьті айналатын жазықтықта жататын және онымен белгілі бүрыш жасайтын бөлшектің қозғалысы
Движение частицы по плоскости, вращающейся вокруг горизонтальной оси и составляющей с ней определенный угол
Keywords: soil-tilling disk; rotary motion; differential equations of motion